Avaliação das boas práticas de manipulação de alimentos em food trucks em Belém-Pa - MONTEIRO, Flávia Soares (2023)
Introduction: The sale of food on the street is an activity predominantly of street vending, carried out on public roads and marketed in places with intense flow of people. Objective: To evaluate the level of knowledge, attitudes and risk practices of food handlers on the good practices of manufacturing food products from Belém-PA. Material and Methods: This is an observational, exploratory, descriptive and crosssectional study carried out with the food handlers of 3 (three) food trucks in the city of Belém-PA. A selfadministered questionnaire and a checklist were applied, both with 37 questions related to good food manufacturing and manipulation practices, in order to assess the knowledge, attitudes and risk practices of the manipulators. The data were analyzed with the help of the BioEstat version 5.3 program and the planning of the data analysis was performed in the SAM (Statistical Analysis Model) technology. Results:9 manipulators participated in the research, 77.77% were female, with ages ranging from 20 to 33 years; 55.55% with lower monthly income 2 minimum wages; 55.55% with experience of 2 to 3 years as a manipulator. 77.77% said they had participated in courses on good practices. Regarding the result of the percentage of correct answers to the questions per block: 1) Personal hygiene 75.8%; 2) Contamination of food, 94.4%; 3) Food hygiene, 56.1%; 4) Hygiene of equipment and utensils, 92.6% and 5) Environmental hygiene, 88.3%. Regarding the checklist, they show that the percentages of adequacies and inadequacies of the 5 blocks of verification of attitudes of risk and good practices did not diverge with the findings in the first questionnaire. Conclusion: The level of knowledge of GMP food truck handlers in general was classified as Good. However, some failures in handling conditions made it clear that the practice stated in the questionnaire does not correspond to that practiced in professional practice, since some habits of hygiene practices practiced by handlers may jeopardize food safety. Therefore, the need for training in order to aggregate information to promote performance improvements in the activities performed is emphasized.